Effect of Intangible Assets, Company Size, Tax Compliance, and Leverage on Transfer Pricing - Mortigor Afrizal Purba; Erni Yanti Natalia; Jontro Simanjuntak (STIE AMKOP, 2022)
This study aims to determine the effect of intangible assets, firm size, tax compliance, leverage on transfer pricing. The data analysis uses multiple linear regressions on 12 manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2015-2019. The results of this study show that intangible assets, firm size, tax compliance, leverage simultaneously have a significant effect on a company’s decision to practice transfer pricing, as well as intangible assets and leverage partially, have a positive and significant effect on transfer pricing. But firm size partly has a negative and significant effect on transfer pricing. Meanwhile, tax compliance has no significant effect on transfer pricing Kata Kunci: intangible assets, firm size, tax compliance, leverage, and transfer pricing